REVISITING GOODBYE, MR. CHIPS: A CRITICAL DISCOURSE ANALYSIS OF CURRICULAR SHIFTS AND CULTURAL REPRESENTATION IN PAKISTANI ENGLISH TEXTBOOKS - Sidra Shafi; Nargas Amanat; Quratulain; Rafia Shaheen; Rehman Asif (International Premier Journal of Languages & Literature, 2026)
This study revisits Goodbye, Mr. Chips within the context of curricular shifts and cultural representation in Pakistani higher secondary English textbooks. The research examines teachers’ perspectives regarding the novel’s cultural relevance, pedagogical significance, psychological contribution, and alignment with contemporary educational priorities in Pakistan. Grounded in the post-positivist paradigm, the study employed a mixed-method research design integrating qualitative interpretation and quantitative analysis to provide a comprehensive understanding of the novel’s educational value. The qualitative component involved documentary and textual analysis interpreted through Norman Fairclough’s Critical Discourse Analysis (CDA) framework, while the quantitative data were collected through a five-point Likert scale questionnaire administered to 20 English teachers of Government Islamia College for Women, Cooper Road, Lahore. The quantitative data were analyzed through SPSS using frequencies, percentages, and mean scores, whereas the qualitative analysis examined cultural, ideological, and educational discourses embedded within the novel. The findings reveal that teachers generally perceive Goodbye, Mr. Chips as a valuable literary text contributing positively to students’ moral development, emotional maturity, empathy, cultural awareness, and literary appreciation. Curricula require contextualized and critically engaging pedagogical approaches aligned with evolving educational priorities in Pakistan. The study further demonstrates that the novel promotes socio-emotional learning and reflective classroom interaction through themes of kindness, resilience, discipline, and professionalism. However, the findings also indicate concerns regarding its effectiveness in promoting critical thinking and its alignment with contemporary curricular demands and modern pedagogical practices. The study concludes that although Goodbye, Mr. Chips retains substantial educational and cultural significance, its relevance within contemporary curricula requires contextualized and critically engaging pedagogical approaches aligned with evolving educational priorities in Pakistan.